Pengaruh Likuiditas, Struktur Aktiva, Struktur Modal Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening Pada Consumer Non-Cyclical yang Terdaftar di Bursa Efek Indonesia - Nur Siti Latipah; Hwihanus; Nekky Rahmiyati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to determine the effect of liquidity, asset structure, and capital structure on firm value with profitability as an intervening variable for non-cyclical consumers listed on the Indonesia Stock Exchange. The data collection technique used is the documentation of the annual report of the Personal Care Products company, which is listed on the Indonesia Stock Exchange (IDX), with five samples selected through purposive sampling. The collected data were analyzed using Partial Least Squares (PLS) analysis. The results showed that liquidity had no significant effect on profitability (0.799 > 0.05). However, liquidity significantly affects firm value (0.023 <0.05). Asset structure has a significant effect on profitability (0.049 <0.05, but asset structure has no significant effect on firm value (0.433 > 0.05). Capital structure has a significant effect on profitability (0.000 <0.05), but capital structure has no significant effect on firm value (0.086 > 0.05). Profitability has a significant effect on firm value (0.001 < 0.05). Profitability has an effect as an intervening variable on the effect of liquidity on firm value (0.226 > 1.96) and the effect of capital structure on firm value (1.971 > 1.96), but profitability has no effect as a variable intervening on the effect of asset structure on firm value (1.747 < 1.96).